Implicações de diferentes doses de decanoato de nandrolona na morfogia cardíaca de ratos idosos - Merlin, Alessandra Paula (2014)
Anabolic androgenic steroids (AAS) are synthetic hormones formed from testosterone and prescribed mainly for diseases affecting the musculoskeletal system, by favoring the increase of muscle mass, resulting in increased muscle strength. Thus, the AAS are beneficial for the elderly patients sarcopenia during aging. However, the AAS have various side effects in various body systems, including the heart morphology, which was the object of this study. Initially, there was the production of a book chapter with the goal of analyzing the cult of the body and the use of aesthetic resources in order to slow the aging process. Subsequently, an experimental study aiming to investigate the influence of different doses of nandrolone decanoate on cardiac morphology in aged rats was performed. To this end, 36 male Wistar rats, 12 months of age were divided into three groups: control, clinical dose (0.714 mg/kg, Nandrolone Decanoate) and high dose (10 mg/kg, Nandrolone Decanoate). Doses were administered intramuscularly once a week for 12 weeks. After the experimental period, samples were processed and heart studied by morphometry and stereology. The results showed a reduction in body weight of high dose group increased relative heart weight/body weight in the high dose group compared to the control. The cardiac mass and cardiac mass/tibia length parameters showed no changes. Regarding the cardiomyocyte diameter and volume density of fibrocytes was observed a significant increase in the treated groups compared to the control, differences between treatment groups were also demonstrated. The results in some parameters investigated show that treatment with nandrolone decanoate induced cardiac hypertrophy which was proportional to the doses used